We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+2
86
2
avatar+74 

*-*>_<

 Feb 21, 2019
 #1
avatar+100570 
+1

y = -x + 7

y = 0.5(x - 3)^2

 

Set the y's equal

 

0.5( x - 3)^2 =  - x + 7     to make this easier, multiply through by 2....this gets rid of the "0.5"

 

(x - 3)^2   = -2x + 14          simplify

 

x^2 - 6x + 9 =  -2x + 14      rearrange as

 

x^2 - 4x - 5  =  0   factor

 

(x - 5) ( x + 1) = 0

 

Setting each factor to 0 and solving for x produces

 

x = 5        or     x   =   - 1

 

And using y = - x + 7

 

When x = 5, y = -5 + 7  = 2

When x = -1, y = -(-1 )  + 7   =  8

 

So.....the solutions are   ( 5, 2)     and  ( -1. 8)

 

 

cool  cool   cool

 Feb 21, 2019
 #2
avatar+74 
+1

Thank a mill

travisio  Feb 21, 2019

4 Online Users